JESUS PRAYER AND STILLNESS OF HEART - Aerthayil, James (Journal of Dharma, 2003)
One of the many fascinating interests of contemporary times is the quest for God-experience. Traditionally, expressions like contemplation, God-experience, etc., have been used for talking about the elite. This is being challenged now. Everybody has a right to God-experience and the consequent calm and peace of mind. To achieve this, the general tendency today is to avoid elaborate traditional methods involving ritualism, and pursue simple forms of prayer. Hence, people everywhere have turned towards the Buddhists in Japan, the Hindu Yogis in India, and the monks of Mount Athos, etc., in their search for lasting experience and interiority. Zen, Yoga, Transcendental Meditation, Jesus Prayer, etc., are no longer strange words to moderns. Irrespective of their religious affiliation, people positively affirm the therapeutic and spiritual value of these methods. In the past few decades, so much has been written about these methods. The Jesus Prayer and Hesychism of the Christian East have also gained considerable attention. However, what exactly is Hesychasm and Jesus Prayer and what is their relationship are not clear to many. Through an historical and theoretico-practical survey, we make an attempt to clarify some of these aspects in the following paragraphs.